1981
DOI: 10.3109/00016358109162267
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic Effect of Denture Base Polymers

Abstract: The cytotoxic potential of autopolymerized pour and dough type resins and heat cured resins was studied by in vitro cell culture techniques. Human epithelial cells (NCTC 2544) were grown in Eagle's minimal essential medium on the surface of the polymer disks. The cell multiplication on the surface of the specimens was measured. One heat cured resin and one pour type resin demonstrated a slight cytotoxic effect. The other polymers gave a moderate cytotoxic effect. The study did not indicate any difference in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…First, the degree of polymerization affects the mechanical and geometric properties of resultant prostheses 29–31 . Second, unreacted monomer may produce undesirable effects in the human body 32–34 . Consequently, resins displaying greater degrees of polymerization may provide substantial clinical advantages.…”
Section: Discussionmentioning
confidence: 99%
“…First, the degree of polymerization affects the mechanical and geometric properties of resultant prostheses 29–31 . Second, unreacted monomer may produce undesirable effects in the human body 32–34 . Consequently, resins displaying greater degrees of polymerization may provide substantial clinical advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Legal regulations for dental laboratories are based on a directive regarding hazardous substances and the technical rules for hazardous materials that is TRGS 900 51. It was reported that MMA vapor in dental practices caused vertigo 52, 53. There is no evidence, however, that serious problems may be caused by inhaling PMMA ingredients, although MMA may irritate the eyes, skin, and respiratory system.…”
Section: Systemic Toxicitymentioning
confidence: 99%
“…The cellular compatibility of solid specimens, aqueous resin extracts, formaldehyde, and MMA were investigated in permanent cells and primary cultures as well 44–46. A study of Hensten‐Pettersen and Wictorin53 revealed clear toxic reactions caused by solid specimens of two orthodontic acrylic resins (one autopolymerizing and another light‐curable) in permanent cultures of fibroblasts and keratinocytes. The cytotoxic effect was greater in autopolymerized resins.…”
Section: Local Toxicity and Tissue Compatibilitymentioning
confidence: 99%
“…They may cause mucosal irritation and sensitization of the oral tissues. [3][4][5][6][7][8][9] Clinical symptoms include burning sensation in the mouth, redness, vesicles, ulceration, swelling and edema. 10 Previous studies have confirmed that resin materials are potentially toxic to various degrees based on their specific composition, 11 porosity, type of polymerization reaction, 12,13 technique used for polymerization 14 and post polymerization material handling.…”
Section: Introductionmentioning
confidence: 99%